El derecho a la protesta y la paralización de servicio público en el sistema jurídico ecuatoriano - Celi Toledo, Ricardo Andrés (2016)
The present investigation carries out tha contain of the social portest right, from its realization through the exercise of rights to freedom of expression and freedom of assembly and association. On the other hand, analyzes the wording of the crime "paralysis of public services". Finally, concludes that the crime is vague and not consistent with the constitutional law about the content of the right to social protest. It has become a mechanism to criminalize and prosecute human rights defenders and leaders of social protests, in the context of the roadblocks.